2018
DOI: 10.1039/c8gc02584c
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of high-performance LiFePO4 nanocrystals in pure water

Abstract: A green and sustainable strategy to synthesize high-performance LiFePO4 nanocrystals in water without by involving any organic solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Fortunately, some progresses on this aspect have been made. [ 157 ] By taking the advantage of microwave‐assisted hydrothermal synthesis, LiFePO 4 nanocrystals with very good electrochemical performance were prepared in pure water without using any organic solvent or surfactants. Moreover, the recycling of valuable Li 2 (SO 4 ) was realized according to the processing route shown in Figure .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, some progresses on this aspect have been made. [ 157 ] By taking the advantage of microwave‐assisted hydrothermal synthesis, LiFePO 4 nanocrystals with very good electrochemical performance were prepared in pure water without using any organic solvent or surfactants. Moreover, the recycling of valuable Li 2 (SO 4 ) was realized according to the processing route shown in Figure .…”
Section: Discussionmentioning
confidence: 99%
“…Reproduced with permission. [ 157 ] Copyright 2018, Royal Society of Chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…For the consideration of the recycling LiFePO 4 , one has however to keep in mind that the particles have to be coated with carbon for enabling electric conductivity. [152][153][154] Tran et al recently reported on the application of deep eutectic solvents, i.e., eutectic mixture of Lewis or Brönsted acids and bases, for green recycling of LIBs, covering both cathodes based on LiCoO 2 and LiNi x Mn y Co z O 2 . [155] Using a mixture of choline chloride and ethylene glycol in a 1:2 ratio as deep eutectic solvent allowed to extract cobalt from used cathodes at a seemingly low temperature of 135 °C.…”
Section: Cathode Materialsmentioning
confidence: 99%
“…Thus, it is of great importance to recycle the lithium source in view of the applied chemistry and environment. In this case, Wang et al reported a green and scalable strategy to synthesis LiFePO 4 , in which the raw materials of LiOH solute could be recycled . Typically, the obtained product of LiFePO 4 nanocrystals was separated by filtration and then the LiOH solute was recovered from the filtrate by separating the impurities of BaSO 4 precipitate with the addition of Ba­(OH) 2 ·8H 2 O.…”
Section: Recycling Valuable Products From the Wastementioning
confidence: 99%
“…In this case, Wang et al reported a green and scalable strategy to synthesis LiFePO 4 , in which the raw materials of LiOH solute could be recycled. 38 Typically, the obtained product of LiFePO 4 nanocrystals was separated by filtration and then the LiOH solute was recovered from the filtrate by separating the impurities of BaSO 4 precipitate with the addition of Ba(OH) 2 •8H 2 O. In this study, 90% of LiOH solute was recovered and reused for the secondary synthesis of LiFePO 4 nanocrystals after adjusting the concentration of recycled LiOH solute to the value of the original run.…”
Section: Highly Valuable Reaction Medium In Chemicalmentioning
confidence: 99%